A proposta pedagógica em escolas de tempo integral: a concepção das tutoras sobre a tarefa para casa na perspectiva da colaboração em Vigotski - Guimarães, Josicleide Farias (2022)
In recent years, the full-time school has been resurrecting more widely and taking effect in several Brazilian cities. Thus, with the extended school day, homework, a pedagogical instrument present in schools since Colonial Brazil, is widely used in the teaching environment. In this teaching modality, the student starts to carry out the homework at the school itself, under the guidance of the tutor. Although it is present in everyday school life, homework, as an object of scientific study, it presents studies that are still incipient and appears in some research works as sub-themes. Faced with the need to reflect on this pedagogical instrument, which is so recurrently used in the teaching environment, and to identify the conceptions that revolve around it, the following guiding research question was elaborated: What is the tutors' conception of homework, in full -time school, in the perspective of collaboration in Vygotsky? Thus, the objective of the research is to investigate the tutors' conception of homework in full- time public schools in João Pessoa, Paraíba, in the early years of Elementary School. From the methodological point of view, the adopted approach is of a qualitative and exploratory nature. The theoretical-methodological focus of this work is based on historical-dialectical materialism, which aims to understand the essence of the investigated object, enabling understanding in its entirety, considering historical aspects, material conditions and the multiple determinations that constituted it. Along the way, authors such as Gramsci (2007), Vigotski (1999, 2000), Leontiev (1978), Saviani (2013, 2019), Duarte (2000, 2002), Gamboa (1989), among others, contributed to the methodological proposal in Schedule. The empirical research was carried out in a school in the city of João Pessoa, Paraíba, with nine tutors who worked in this unit as research subjects. To obtain the information, a semi-structured interview was used and, for the analysis of the information, dialectical hermeneutics. The research made it possible to verify that there is a consensus among the tutors on the importance of the homework, due to the fact that, in full-time school, the student performs school activities with the tutor's mediation, ensuring that the activities are carried out daily. However, the organization of the homework assignment is not jointly defined, leaving it up to the teacher to plan it and, to the tutor, to ensure that the students complete it. This proposition clearly focuses on the division of teaching work, since it is up to the teacher to plan and the tutor to carry out this activity. This finding highlights the importance of full-time school including homework in school planning and that this be constructed by teachers and tutors, bearing in mind that they are required to have a degree in Pedagogy.